Linguistic Patterns’ Role in Arabic-Chinese Translation - Lingling, Lao (Journal of Arabic Language Sciences and Literature, 2023)
The study of linguistic patterns between Chinese and Arabic plays an important role in translation since ancient times until now. This research will study linguistic patterns based on the characteristics of the Chinese and Arabic languages to clarify their decisive role in translation. It will also compare some linguistic patterns in the two languages, which helps us to know the language into which it is translated and to understand it deeply.
Keywords: Linguistic Patterns; Arabic; Chinese; Translation